O Beijo: superação crítica de uma prática de ensino de artes visuais - Ricardo Grassi Martins (2025)
This study aims to provide the foundation for overcoming a pedagogical practice in art education, using the artistic monuments of the city of Campo Grande – MS as curricular content, with an emphasis on the artwork “O Beijo” by Pedro Guilherme Garcia Góes. As the theoretical-methodological foundation for the critique of art education, we adopt the historical-critical and ontological approach. The study addresses issues such as artistic and aesthetic objectification and human development, while also exploring elements like catharsis, artistic experience, and territoriality/place, articulated through the dialectic between the singular, the particular, and the universal. It examines a local artist in relation to concrete totality. This work is developed in the theoretical field, methodologically grounding the critique of the triangular approach, guiding documents, and an entire school of thought. By returning to practice, we aim to foster emancipatory education. In doing so, we believe we contribute to art education from a historicalcritical perspective, providing both theoretical and practical support. Keywords: Pedro Guilherme; Sculpture; Historical-Critical Pedagogy.